Water deficit and salinity stresses modulate growth, physiology, and phytochemical composition of Lavandula coronopifolia Poir. grown in pots under controlled conditions - Debbagh-Nour, Hafsa; El Mouttaqi, Ayoub; Lazaar, Karima; Mnaouer, Ihssane; Malki, Sanaa; Ducousso, Marc; Boukcim, Hassan; Hirich, Abdelaziz (Frontiers in Plant Science, 2026)
Lavandula coronopifolia Poir. is a medicinal evergreen shrub, wildly distributed in rocky and arid environments. It belongs to the Lamiaceae family, known by the large array of bioactive compounds it contains. Drought and salinity present major threats in arid zones and severely penalize the potential yield of naturally growing desertic plants; however, it may affect the synthesis and accumulation of their metabolites. Few studies have investigated the response of Lavandula species to abiotic stresses and to the best of our knowledge, none have been conducted on L. coronopifolia. Our study aims to investigate various responses of this species to water deficit and salt stress under controlled conditions. Two distinct experiments were conducted in a growth chamber, each lasting one month. The first one focused on water stress, with plants subjected to four water treatments: control (100% field capacity (FC)), moderate water deficit (50% FC), severe water stress (25% FC), and very severe water stress (alternating irrigation to 50% FC for one week followed by cessation of watering for the next week). These treatments were arranged in a randomized complete block design (RCBD) with 3 blocks, each containing 3 replicates per treatment, resulting in 9 replications per treatment. The second experiment investigated the effect of salt stress, where plants were exposed to four NaCl concentrations: 0, 5, 10, and 20 dS/m. This experiment was also conducted using an RCBD, with 4 blocks and 4 replicates per treatment within each block, giving a total of 16 repetitions per treatment. Growth parameters, oxidative stress indicators as well as secondary metabolite content were determined. Results have shown that under both water and salt stress conditions, plant fresh and dry weights decreased significantly. Malondialdehyde levels increased under intense stress in both experiments, indicating enhanced lipid peroxidation. Protein content increased under water stress but showed no change under salt stress. Phenolic and flavonoid contents increased with water stress but decreased with salt stress. Antioxidant activity remained stable under water stress and showed a significant increase with salt stress. These findings enhance our understanding of how plants modulate various traits in response to distinct water and salt stress conditions.